Breastfeeding duration, age of starting solids and high BMI risk and adiposity in Indian children. Issue 2 (7th October 2011) - Caleyachetty, Amrit; Krishnaveni, Ghattu V.; Veena, Sargoor R.; Hill, Jacqui; Karat, Samuel C.; Fall, Caroline H.D.; Wills, Andrew K.
Abstract This study utilized data from a prospective birth cohort study on 568 Indian children, to determine whether a longer duration of breastfeeding and later introduction of solid feeding were associated with a reduced higher body mass index (BMI) and less adiposity. Main outcomes were high BMI (>90th within‐cohort sex‐specific BMI percentile) and sum of skinfold thickness (triceps and subscapular) at age 5. Main exposures were breastfeeding (six categories from 1–4 to ≥21 months) and age of starting regular solid feeding (four categories from ≤3 to ≥6 months). Data on infant‐feeding practices, socio‐economic and maternal factors were collected by questionnaire. Birthweight, maternal and child anthropometry were measured. Multiple regression analysis that accounted for potential confounders demonstrated a small magnitude of effect for breastfeeding duration or introduction of solid feeds on the risk of high BMI but not for lower skinfold thickness. Breastfeeding duration was strongly negatively associated with weight gain (0–2 years) [adjusted β = –0.12 standard deviation, 95% confidence interval (CI): –0.19 to –0.05 per category change in breastfeeding duration, P = 0.001], and weight gain (0–2 years) was strongly associated with high BMI at 5 years (adjusted odds ratio = 3.8, 95% CI: 2.53–5.56, P < 0.001). In our sample, findings suggest that longer breastfeeding duration and later introduction of solids has a small reduction on later high BMI risk and a negligible effect on skinfold thickness. However, accounting for sampling variability, these findings cannot exclude the possibility of no effect at the population level.